Different principles of information integration in implicit and explicit attitude formation - Betsch, Tilmann; Kaufmann, Martina; Lindow, Frank; Plessner, Henning; Hoffmann, Katja (European journal of social psychology, 2006)
Recent research provides evidence that implicit attitude formation is guided by a summation principle (Betsch, Plessner, Schwieren, & Gütig, 2001). This finding contradicts models claiming that attitudes form from the average value of stimulus information (e.g., Anderson, 1981). In this paper, we show that the application of an integration rule depends on the mode of processing (implicit vs. explicit). In three experiments, participants encode sequences of return values produced by shares on the stock market. Results jointly indicate that evaluative judgments follow an averaging principle when attitudes were formed explicitly, either on memory content (Exp. 1) or the relevant sample of information (Exp. 2). In Experiment 3, we varied the processing mode within participants. An attitude reversal effect was found by varying the mode of processing for the same set of stimuli. After implicit attitude formation, participants evaluated the share with a higher sum of return values more positively than the share with a higher average value. This pattern reversed when participants explicitly evaluated the same shares. Copyright © 2006 John Wiley & Sons, Ltd.
First published: 18 August 2006
Gesehen am 22.07.2022